Early and late basilar artery thrombectomy time window outcomes - Mierzwa, Adam T.; Rao, Rahul; Al Kasab, Sami; Nelson, Ashley; Ortega-Gutierrez, Santiago; Vivanco-Suarez, Juan; Farooqui, Mudassir; Jadhav, Ashutosh P.; Desai, Shashvat; Toth, Gabor; Alrohimi, Anas; Nguyen, Thanh N.; et al. (Frontiers in Neurology, 2024)
Importance Stroke-to-recanalization time is a strong predictor of outcomes in anterior circulation large-vessel occlusion (LVO). The authors aimed to evaluate functional outcomes in early (<6 h) vs. late (6–24 h) time windows for thrombectomy-treated basilar artery occlusions. Methods Patients were derived from the Posterior Circulation Ischemic Stroke Evaluation: Analyzing Radiographic and Intra-procedural Predictors of Mechanical Thrombectomy (PC-SEARCH) Registry and retrospectively analyzed early and late basilar artery thrombectomy time windows cohorts. Patients were dichotomized based on the last known well and correlated to 90-day functional outcomes (mRS 0–3). A multiple logistic regression analysis was performed. Results A total of 405 patients were included in this study: 216 and 189 patients in the early and late time windows, respectively. Baseline demographic, stroke, radiographic, and intraprocedural characteristics were similar between the groups. A total of 99 (46%) and 79 (42%) patients in the early and late time windows, respectively, achieved favorable functional outcomes at 90 days (p = 0.41), and multiple logistic regression analysis did not reveal differences between cohorts (OR: 0.74; 95% CI: 0.46–1.19; p = 0.22). Symptomatic hemorrhage (7% vs. 5%; p = 0.69) and neurological complications (8% vs. 9%; p = 0.83) were similar between the groups; however, hospital complications were more common in the early time window cohort (22% vs. 13%; p = 0.01). Conclusion The early and late thrombectomy time windows can achieve similar rates of 90-day favorable functional outcomes. However, timely thrombectomy influences the likelihood of achieving excellent functional outcomes (mRS ≤ 2) within the early time window.